P2-S9.11 HIV infection and violence against married/cohabiting women: findings from a national household survey in Rwanda. (10th July 2011) - Kayibanda, J F; Alary, M; Bitera, R
Abstract : Objectives: We used the third Rwanda demographic and health survey (DHS) data to examine relationship between violence, gender attitudes and HIV prevalence among women and men in union. Methods: The third Rwanda DHS is a nationally representative household-based survey conducted in 10 272 households in 2005. Analyses were restricted to 2715 women and 2461 men who were legally married or cohabiting. HIV prevalence was the dependent variable whereas sexual risk factors, gender attitudes, emotional and domestic violence were independent variables. A face-to-face interview covered socio-demographic characteristics, sexual risk behaviour, domestic violence and gender attitude. Domestic violence was measured by questions from the Conflict Tactics Scale Questionnaire. HIV antibodies testing was performed using ELISA tests. Logistic regression was used for statistical analysis. Results: HIV prevalence was significantly higher among women who reported ever having experienced any form of emotional violence (4.7% vs 2.1%; p=0.019), who reported ever been threaten by their husband or cohabiting partner (6.1% vs 2.3%; p=0.026) and among those who reported that their fathers beat their mothers (3.4% vs 1.9% p=0.029). HIV prevalence was higher among men who reported that they are justified to hurt or beat their wives if they argue with them (10.1% vs 2.9 p=0.03). After adjustment for age, geographic area, number of lifetime partners, history of genital ulcers in the previous year, women who experienced at least one form of violence (either, emotional, inter parental, or intimate partner violence) demonstrated a much higher HIV prevalence [adjusted OR (AOR): 2.75; 95% CI 1.08 to 7.02]. Compared to those who confirmed that it is not justified for a husband to hurt or beat his wife if she argues with him, men who agreed with this statement had a fourfold higher HIV-prevalence (AOR: 4.15; 95% CI 1.69 to 10.17). Conclusion: Violence experienced by women and the acceptance of wife beating by men are independent risk factors for HIV infection among married/cohabiting population in Rwanda. Interventions to prevent any form of violence towards women and hostile gender attitudes should be integrated into HIV programs.